THE EFFECT PROBLEM-BASED LEARNING MODEL ON PROBLEM-SOLVING ABILITY MATHEMATICS STUDENT CLASS IX SMP NEGERI 6 MEDAN - Elfrida Monika Yulianti Sinaga; Ani . Minarni (INSPIRATIF : JURNAL PENDIDIKAN MATEMATIKA, 2017)
ABSTRACT This research is an experiment research that aims to determine the significant effect of problem-based learning model on mathematic problem solving ability of grade IX students of SMP Negeri 6 Medan. The population in this study is the entire class IX SMP Negeri 6 Medan consisting of 11 classes. Sampling is done randomly by simple random sampling method and many samples in this research consist of 2 classes, that is class IX-J as control class with conventional learning that is direct learning model and class IX-K as experiment class with problem-based learning model, the number of students in each class is 36 students. The instrument used in this study is a test description of 3 test problem math problem solving abilities that have been declared valid. Based on the test data of mathematical problem solving ability, the average value in the control class is 51.83, while the average value in the experimental class is 75.50. By using the calculation of one-way hypothesis test, obtained at 6.86 and 1.66691 at the real level = 0.05 so. Thus rejected and accepted, it means there is a significant effect of problem-based learning model of mathematical problem solving ability of students of class IX SMP Negeri 6 Medan.Keyword: mathematics problem solving ability, problem based learning model ABSTRAKPenelitian ini merupakan penelitian eksperimen yang bertujuan untuk mengetahui pengaruh yang signifikan model pembelajaran berbasis masalah terhadap kemampuan pemecahan masalah matematik siswa kelas IX SMP Negeri 6 Medan. Populasi dalam penelitian ini adalah seluruh kelas IX SMP Negeri 6 Medan yang terdiri dari 11 kelas. Pengambilan sampel dilakukan secara acak dengan metode simple random sampling dan banyak sampel dalam penelitian ini terdiri dari 2 kelas, yaitu kelas IX-J sebagai kelas kontrol dengan pembelajaran konvensional yaitu model pembelajaran langsung dan kelas IX-K sebagai kelas eksperimen dengan model pembelajaran berbasis masalah, jumlah siswa pada masing-masing kelas adalah 36 orang siswa. Instrumen yang digunakan dalam penelitian ini adalah tes uraian  sebanyak 3 soal tes kemampuan pemecahan masalah matematik yang telah dinyatakan valid. Berdasarkan data tes kemampuan pemecahan masalah matematik, nilai rata-rata di kelas kontrol sebesar 51,83, sedangkan nilai rata-rata di kelas eksperimen sebesar 75,50. Dengan menggunakan perhitungan uji hipotesis satu arah, diperoleh  sebesar 6,86 dan  sebesar 1,66691 pada taraf nyata = 0,05 sehingga .  Dengan demikian  ditolak dan  diterima, artinya terdapat pengaruh yang signifikan model pembelajaran berbasis masalah terhadap kemampuan pemecahan masalah matematik siswa kelas IX SMP Negeri 6 Medan.Kata kunci: kemampuan pemecahan masalah matematik, model pembelajaran berbasis masalah